Felt Justice : Correlations Between University Students and University Personnel - Reunanen, Tero; Taatila, Vesa (Springer, 2021)
Humans typically have a need to be heard and recognized. This need is often felt as a need of fair treatment of people, especially in relationships between leaders and followers. Former research has shown a correlation of felt justice between students and staff. This means that in the situations where school staff members feel fairness and justice from their leadership, students also feel same from the staff. Typically, people feel to be treated well, just when they believe that their leaders or teachers hear their views and opinions. This research was done by utilizing two different questionnaire tools, one for staff and one for students. Data was gathered in 2019 and 2020 in annual organizational surveys. The overall research question is: Is there a correlation between felt justice of staff and students’ satisfaction? This article shows the correlations and discusses the results of these correlations. Future research aspects and practical recommendations will also be issued in the paper.
Keywords: fairness; leadership; management; Organizational behavior; justice; fi=Tuotantotalous|en=Industrial Management|